Factors Affecting Taxpayer Compliance: A study during the Covid-19 Pandemic - Kartim, Kartim (Advances in Taxation Research, 2023)
Purpose: This study aims to analyze the impact of various factors, including tax knowledge, tax policy, taxpayer attitudes, tax authority services, and the implementation of the self-assessment system, on taxpayer compliance among MSMEs in Jayapura City during the COVID-19 pandemic. Research Design and Methodology: A quantitative approach was employed, with primary data collected through questionnaires distributed to 92 MSME taxpayers in Jayapura City. Multiple linear regression analysis assessed the relationships between independent variables and taxpayer compliance. The study also conducted descriptive statistical tests, validity and reliability tests, normality, heteroscedasticity, and multicollinearity tests. Hypothesis testing was performed using the coefficient of determination, partial, and simultaneous tests. Findings and Discussion: The findings indicate that tax knowledge, tax policy, taxpayer attitudes, tax authority services, and the self-assessment system positively and significantly impact taxpayer compliance. The results suggest that MSME taxpayers in Jayapura City exhibit higher compliance when these factors are effectively implemented and well-communicated. The study highlights the importance of fostering taxpayer awareness, ensuring clear tax policies, providing efficient tax services, and strengthening the self-assessment system to enhance voluntary compliance. Implications: The study contributes to academic research and policy development by emphasizing education, administrative efficiency, and policy clarity in improving taxpayer compliance. The findings suggest that tax authorities should optimize digital platforms for tax education and outreach. Future research should explore additional factors, such as legal enforcement and technological advancements, in promoting long-term compliance.